Analysis of Compliance with DSN-MUI Fatwa in the Murabahah Financing Contract (Case Study at BPRS Amanah Ummah) - Agung Rahmatullah (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The murabahah contract is the most dominant financing product used by Islamic banks, making compliance with DSN-MUI Fatwa essential for maintaining the integrity of Islamic financial institutions. However, studies indicate gaps between normative fatwa provisions and operational practices, particularly concerning wakalah mechanisms and financing supervision. This study aims to analyze BPRS Amanah Ummah's compliance with DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 in implementing murabahah financing contracts and identify supporting and hindering factors. Method: This research employs a qualitative approach with a case study design at BPRS Amanah Ummah, Bogor Regency. Data were obtained through in-depth interviews, observations, and documentation with informants including leaders, the Sharia Supervisory Board (DPS), financing employees, and customers. Data analysis followed the Miles and Huberman interactive model through data reduction, presentation, and conclusion drawing stages. Results: The findings indicate that the implementation of murabahah contracts at BPRS Amanah Ummah generally complies with DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000, particularly in margin transparency, property ownership, and financing supervision aspects. Sharia compliance is supported by established SOPs, the active role of the Sharia Supervisory Board, and routine employee coaching. Challenges remain, including potential side streaming in wakalah contracts, low community sharia financial literacy, and administrative obstacles in the financing process. Conclusion: BPRS Amanah Ummah demonstrates a high level of compliance with DSN-MUI Fatwa in murabahah contract implementation, reflected not only in formal contractual aspects but also in efforts to maintain transparency, justice, and benefit in accordance with sharia principles. Strengthening sharia financial literacy, optimizing financing supervision, and improving sharia governance remain essential for sustaining substantive sharia compliance.